Robust anti-icing superhydrophobic aluminum alloy surfaces by grafting fluorocarbon molecular chains. (December 2020) - Rico, Víctor; Mora, Julio; García, Paloma; Agüero, Alina; Borrás, Ana; González-Elipe, Agustín R.; López-Santos, Carmen
Highlights: Robust anti-icing superhydrophobic alloy surfaces by grafting fluorocarbon molecular chains. anti-icing textured aluminum surface by grafted fluorocarbon molecules. durability and stability of mobile fluorocarbons hindering ice nucleation. checking icephobicity through ice accretion tests in simulated environments. Abstract: Infusion of low surface tension liquids in nanostructured surfaces is currently used to promote an anti-icing response, although the long term stability of these systems is often jeopardized by losses of the infused liquid. In this work, we propose an alternative to the infusion procedure to induce a more effective and long lasting anti-icing capacity. The method consists of a combination of surface nanostructuration with the chemical grafting of fluorocarbon molecules. Al6061 substrates have been subjected to laser roughening and further modified with a nanostructured Al2 O3 thin film to achieve a dual roughness and porous surface state. These surfaces have been subjected to a grafting treatment with perfluorooctyltriethoxysilane (PFOTES) vapor or, for comparative purposes, infused with a low surface tension liquid. A comparative analysis of the wetting, water condensation and anti-icing properties of these two systems showed an outstandingly better performance for the grafted surfaces with respect to the infused ones. Grafted surfaces were markedly superhydrophobic and required higher water vapor pressures to induce condensation. When looking for their anti-icing capacity, they presented quite long freezing delay times for supercooled water droplets (i.e. almost four hours) and exhibited a notably low ice accretion in a wind tunnel test. The high aging resistance and durability of these grafted surfaces and the reproducibility of the results obtained when subjected to successive ice accretion cycles show that molecular grafting is an efficient anti-icing methodology that, in aggressive media, may outperform the classical infusion procedures. The role of the fluorocarbon chains anchored on the surface in inducing an anti-icing functionality is discussed. Graphical abstract: Image, graphical abstract